PENERAPAN MEDIA KEPING BERWARNA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR (Studi Eksperimen Pada Bilangan Bulat Di Kelas IV SDN Sukasari Kec. Cipatat) - Rohartati, Sri (Jurnal Penjaminan Mutu, 2017)
The low learning outcomes in mathematics at the State Elementary School in the material Sukasari summation of integers and the results of their study have not yet reached KKM (minimum completeness criteria) to overcome these problems, the researchers used instructional media as a tool to improve the learning outcomes of students. The research design used in this study are nonequivalent control group design. This research was conducted in two classes, experimental and control classes. Both of these classes are treated differently, grade control using conventional learning while the experimental class using the Media Chips Color. Data collection techniques used in this research is the observation and tests. To collect data in this study, the use of research instrument shaped observation sheets and test questions. Based on the analysis of data there are significant differences between the results of the pretest and posttest experimental class and there are differences in learning outcomes between the control group and the experimental group after treatment so that there are significant media use colored tile to the study of students in mathematics in elementary school then the hypothesis can be accepted.